PENGGUNAAN H2O2 PADA PROSES PENDINGINAN IKAN LAYANG (Decapterus sp.) - Lovi Sandra; Rahwan Rahwan (Faculty of Science and Technology University Ibrahimy, 2015)
The study aims to determine the use of H2O2 in the process of cooling fish float (Decapterus sp) in Trade Enterprises Mr Didik Rudianto, Situbondo, East Java. The study was conducted from 06 February to May 6, 2015. The method used in this research is survey method. Types of data collected consist of primary data and secondary data. Primary data was collected by field observations, interviews, direct participation, and documentation. While secondary data collected by the various literature searches related to research materials. The results showed that the cooling process fish include: procurement of raw materials, transportation, weighing, provision of ice detached, laying fish float, giving the salt, and the provision of or addition of hydrogen peroxide (H2O2) they are urgent or necessary function for the belly of the fish do not break when fish delivery mileage considerably. Dose use of hydrogen peroxide (H2O2) in the process of cooling fish ie + 50 ml of hydrogen peroxide per 1 quintal of fish by dilution + 3 liters of water. The use of hydrogen peroxide with a dose of it is prohibited by Decree of the Minister of Marine and Fisheries of the Republic of Indonesia number 52 / KEPMEN-KP / 2014.